Caregiving information needs of family caregivers of adolescent patients with suicide attempts: a qualitative study in China - Xiaoning Wang; Qunfang Miu; Jiannv Wang; Xiaoyu Huang; Wenru Xie (BMC Nursing, 2024)
Abstract Background In the cultural milieu of China, family caregivers assume a pivotal role in the post-adolescent suicide attempt recovery journey. Nevertheless, they frequently encounter a dearth of requisite knowledge and information pertaining to the appropriate caregiving protocols for these adolescents. Notwithstanding, scholarly investigation into the informational requisites of this demographic concerning caregiving remains significantly constrained. Methods Between September and December 2023, a phenomenological approach was applied in qualitative research. Semi-structured interviews were undertaken with 15 family caregivers of adolescents who had experienced suicide attempts. The amassed data underwent systematic organization and analysis through the utilization of the Colaizzi method. Results Four primary themes were identified: (1) negative emotional encounters; (2) requirements for addressing dilemmas; (3) addressing the needs of the unknown; and (4) insufficient access to support. Conclusions Family caregivers experience complex negative emotions upon learning about a teenager’s suicide attempt. Throughout the caregiving process, they face numerous challenges, with apparent lack of external support, leading to an increased urgent need for caregiving information. Healthcare professionals, especially nurses, should actively identify and respond to the informational needs of family caregivers when caring for adolescents who have attempted suicide. This includes providing education on various coping mechanisms and support strategies, as well as assisting them in better understanding how to effectively manage the stress and challenges of caregiving. By doing so, healthcare professionals can help alleviate the psychological and emotional burden on family caregivers, thereby enhancing their caregiving abilities and overall well-being.